Mineralization of the stylohyoid complex in a population from Cuenca-Ecuador - Castro-Espinoza, Erika (2020)
The stylohyoid complex is a bony and ligamentous structure, formed by several anatomical entities such as the styloid process, the stylohyoid ligament and the horn of the hyoid. The styloid process originates in the tympanic portion of the temporal bone and measures an average of 25 mm; sometimes it may be increased in length, a situation that may or may not have pain itself. Objective: To determine the prevalence of mineralization of the stylohyoid complex of patients at the country of Ecuador using digital panoramic radiographs. Material and methods: Analysis of 2025 digital panoramic radiographs of patients of both sexes, between 12 and 92 years of age, from the period 2015-2016. It was considered as mineralized stylohyoid complex, when it exceeded 25mm. Results: Of the 2025 panoramic radiographs, it was concluded that 1206 (59.6%) radiographs showed some type of mineralization of the stylohyoid complex. Of these 1288 (63.6%) belong to the female sex and 737 (36.4%) to the male sex. The most frequent presentation was bilateral. In addition, it was found that in older adults the prevalence reached 76%. Conclusions: In the present study it is shown that there is a high prevalence of mineralization of the stylohyoid complex in the population studied.